Optimization of the Morphological Parameters of a Metal Foam for the Highest Sound Absorption Coefficient Using Local Search Algorithm - Mohammad Javad JAFARI; Ali KHAVANIN; Touraj EBADZADEH; Mahmood FAZLALI; Mohsen Niknam SHARAK; Rohollah Fallah MADVARI (Archives of Acoustics)
Due to its unique features, the metal foam is considered as one of the newest acoustic absorbents. It is a navel approach determining the structural properties of sound absorbent to predict its acoustical behavior. Unfortunately, direct measurements of these parameters are often difficult. Currently, there have been acoustic models showing the relationship between absorbent morphology and sound absorption coefficient (SAC). By optimizing the effective parameters on the SAC, the maximum SAC at each frequency can be obtained. In this study, using the Benchmarking method, the model presented by Lu was validated in MATLAB coding software. Then, the local search algorithm (LSA) method was used to optimize the metal foam morphology parameters. The optimized parameters had three factors, including porosity, pore size, and metal foam pore opening size. The optimization was applied to a broad band of frequency ranging from 500 to 8000 Hz. The predicted values were in accordance with benchmark data resulted from Lu model. The optimal range of the parameters including porosity of 50 to 95%, pore size of 0.09 to 4.55 mm, and pore opening size of 0.06 to 0.4 mm were applied to obtain the highest SAC for the frequency range of 500 to 800 Hz. The optimal amount of pore opening size was 0.1 mm in most frequencies to have the highest SAC. It was concluded that the proposed method of the LSA could optimize the parameters affecting the SAC according to the Lu model. The presented method can be a reliable guide for optimizing microstructure parameters of metal foam to increase the SAC at any frequency and can be used to make optimized metal foam.